Slow‐Moving Phase Boundary in Li4/3+xTi5/3O4 (Small Methods 10/2021). Issue 10 (28th October 2021) - Joshi, Yug; Lawitzki, Robert; Schmitz, Guido
Abstract : Inside Back Cover In article number 2100532, Joshi and co‐workers developed a methodology to study lithium transport using optical microscopy. It unravels temperature dependent diffusion and barrier coefficients for the two phases and the phase boundary. Electrode‐size dependent, slow/linear migration of the phase boundary, in the initial stages of lithiation, is observed. It is postulated that such migration is controlled by the concentration gradient in the Li4/3+δ Ti5/3 O4 phase formed ahead of the phase boundary.